DAKWAH KONTEMPORER DI LAYAR KACA: ANALISIS DRAMA TELEVISI 'PREMAN PENSIUN 2' SEBAGAI MEDIA PENYEBARAN PESAN KEBAIKAN DAN REPRESENTASI HIJRAH - Irham, Muhammad; M. Agung Pramana; Pipir Romadi (JURNAL MANAJEMEN DAKWAH, 2023)
This paper analyzes the emergence and development of the contemporary da'wah movement on Indonesian Television Stations. Specifically, this paper highlights the meaning of goodness implied in the Television Drama 'Preman Pensiun 2'. This study is conducted to see how the da'wah movement in the movie 'Preman Pensiun 2' spreads through the media has developed. This article will answer questions such as How the representation of hijrah in the television drama 'Preman Pensiun 2'? What is the role of television drama actors in expressing the form of hijrah? And what a message of kindness it generates. The data of this research is obtained from ethnography studies related to the Television Drama 'Preman Pensiun 2' and data relevant to the topic of study. The results of this study show that the television drama 'Preman Pensiun 2' is a form of contemporary da'wah development that aims to increase piety for the people who watch. This television drama also shows how a person's struggle in proselytizing through the hijrah process is packed with religious, social, and popular culture aspects. This television drama is packed with comedy and shows the commodification of religion that occurs in this television drama. Then, this television drama depicts a story that is close to the reality we experience, so that it becomes a reference so that the audience becomes interested in taking action according to the television drama.